2014
DOI: 10.1007/s12017-014-8288-8
|View full text |Cite
|
Sign up to set email alerts
|

Distinct Patterns of Sirtuin Expression During Progression of Alzheimer’s Disease

Abstract: Aging is one of the major risk factors for Alzheimer's disease (AD). Sirtuins are associated with prolonged life span. To examine whether the expression levels of sirtuins associate with the progression of AD or not, we performed a comparative immunoblotting and immunohistochemical study of SIRT1, 3, and 5 in the entorhinal cortex and hippocampal subregions and white matter in 45 cases grouped according to Braak and Braak stages of neurofibrillary degeneration. In addition, we compared the expression levels wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
84
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 115 publications
(86 citation statements)
references
References 60 publications
2
84
0
Order By: Relevance
“…We found here that the IOD of SIRT1 or SOD-1 immunostaining in the temporal and frontal cortices, and hippocampus, but not the cerebellum, were both significantly correlated with the Braak stage, which supported by previous reports 37. Since the cortices and hippocampus, but not the cerebellum, are regions of the brains of patients with AD obviously affected,43 SIRT1 and/or SOD-1 may be involved in the pathology of AD.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…We found here that the IOD of SIRT1 or SOD-1 immunostaining in the temporal and frontal cortices, and hippocampus, but not the cerebellum, were both significantly correlated with the Braak stage, which supported by previous reports 37. Since the cortices and hippocampus, but not the cerebellum, are regions of the brains of patients with AD obviously affected,43 SIRT1 and/or SOD-1 may be involved in the pathology of AD.…”
Section: Discussionsupporting
confidence: 91%
“…SIRT1 is expressed at lowered levels in the brains of patients with AD, indicating that loss of this factor may play a key role in the pathogenesis and progression of AD 36. A previous study on brain tissue derived from individuals with AD found decreased protein expression of SIRT1 in the hippocampus during the progression of AD 37. Similar to our present findings, reduced expression of SIRT1 in the temporal and frontal cortices, and hippocampus was observed, but not cerebellum of patients with AD in comparison with the age-matched control groups.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, it is reported that ROS originated from [4]. A recent study concluded that sirt3 expression is decreased during the progression of AD in human study [21]. Interestingly, sirt3 involves in ROS production and detoxification, in large part by targeting proteins that regulate intracellular antioxidant machinery [10].…”
Section: Discussionmentioning
confidence: 99%
“…SIRT6 also facilitates chromatin opening at the site of DNA damage by recruiting sucrose nonfermenting protein 2 homologue (SNF2H; also known as SMARCA5) 137 , and it facilitates the recruitment of downstream factors, such as TP53BP1, BRCA1 and replication protein A (RPA) 137 . In Alzheimer disease, levels of different members of the sirtuin family are dysregulated 138,139 and it has been suggested that modulation of sirtuin levels or activity, through pharmacological innervation or calorie restriction, may offer new approaches to the prevention or treatment of neurodegenerative disorders. Collectively, these data suggest that the sirtuins, long associated with alterations in the rate of ageing, are also important in maintaining genomic integrity via their effects on the DNA repair process.…”
Section: Changes In Non-genomic Factorsmentioning
confidence: 99%